2020
DOI: 10.1002/mp.14066
|View full text |Cite|
|
Sign up to set email alerts
|

Automated left ventricular myocardium segmentation using 3D deeply supervised attention U‐net for coronary computed tomography angiography; CT myocardium segmentation

Abstract: Purpose Segmentation of left ventricular myocardium (LVM) in coronary computed tomography angiography (CCTA) is important for diagnosis of cardiovascular diseases. Due to poor image contrast and large variation in intensity and shapes, LVM segmentation for CCTA is a challenging task. The purpose of this work is to develop a region‐based deep learning method to automatically detect and segment the LVM solely based on CCTA images. Methods We developed a 3D deeply supervised U‐Net, which incorporates attention ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Semi-automatic segmentation of the LV using a machine learning model for defining epi- and endocardial contours has been validated extensively. Several studies have reported high comparability to a manual segmentation of the LV versus a machine learning approach [20] , [21] , [22] , [23] . It must also be noted that manually drawing epi- and endocardial contours is a time-intensive process of usually around 20–30 min [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Semi-automatic segmentation of the LV using a machine learning model for defining epi- and endocardial contours has been validated extensively. Several studies have reported high comparability to a manual segmentation of the LV versus a machine learning approach [20] , [21] , [22] , [23] . It must also be noted that manually drawing epi- and endocardial contours is a time-intensive process of usually around 20–30 min [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the excellent image segmentation performance of FCN, the basic architecture of most medical image segmentation networks is based on it 22–32 . Similarly, in the OAR segmentation of the head and neck and the lung, researchers proposed a variety of FCN‐based segmentation methods 6,7,15 33–36 .…”
Section: Related Workmentioning
confidence: 99%
“…This is a technique that is widely utilized in the segmentation of medical images. Jun et al [9] came up with a 3D deep attention technique, which is an improvement on more conventional approaches. Cui et al [10] coupled the attention mechanism with Attention U-Net to segment left ventricular myocardial contours from coronary computed CT angiography.…”
Section: Introductionmentioning
confidence: 99%